Cooperation Strategy of Libraries in Developing Rural Libraries Done By Documentation and Archive Library in Malang Regency. - Tri Mega Asri (Program Pendidikan Vokasi Universitas Brawijaya, 2017)
Imbalance collection with the number of 21 155 copies and limited facilities and infrastructure which is also owned also affect the process of delivering information to the public especially remote rural communities that exist in the area of Malang. Library cooperation conducted Public Library Malang with village library through the empowerment and development activities is to go through three stages: first planning activities undertaken are filling the questionnaire and screening in order to determine the elected village library. Both actuating, ie rotating book lending activities by Public Library of Malang with the number of 100 copies borrowing library materials that his later be borrowed right to elect the village library. Third monitoring and evaluation, namely monitoring and evaluation activities. Conclusion Taman Baca Masyarakat Pondok Sinau which is a sample of cooperative activities libraries have a total collection of 475 copies with the presentation of a collection of general knowledge is more dominant, with lending activities book innings by the Public Library of Malang with the number of 100 copies is expected to support the collection, complements the percentage of collection and update the information on the TBM to assist communities in meeting the need for information. Suggestions for further activities are still carrying out accompaniment library cooperation activities with the intention that the library established cooperation capable of running in accordance with the purpose of library cooperation, and to evaluate how much of this cooperation used by the community.